Extended spectrum β-lactamase (ESβL)-producing E. coli causing urinary tract infection among pregnant women and pediatric patients in public hospitals in northern Jordan - Waleed Al Momani; Ayah Elayan; Rama Al Titi; Ismail Malkawi; Leen Al momani; Mohammad Al-Magableh (PLoS ONE, 2025)
Background Urinary tract infections (UTI’s) imply the invasion and multiplication of bacteria in the individual’s urinary tract, the incidence of UTI’s is mainly determined by sex and age being the highest in pregnant females. E. coli is the most frequently encountered causative agent of UTI’s and recent data depict an increase in antimicrobial resistance. Objectives This study aims to identify the most common pathogens associated with UTI’s in pregnant women and children and to reveal the resistance patterns, and effective treatments and to detect resistance genes in E. coli. Methods This study was conducted in public-teaching Hospitals in northern Jordan during the period from the 1st of March 2024 to the 5th of April 2024. Urine samples were collected in a sterile urine container or using a special tube for pediatric samples. Each sample was cultivated on MacConkey, blood and mannitol salt agar plates, all plates were incubated aerobically at 37°C for 24 hours and identified using standard microbiological protocols. All isolates were tested for antimicrobial susceptibility. Polymerase chain reaction was performed to confirm all E. coli isolates by the detection of universal stress protein (uspA) gene and to detect ESβL genes TEM, SHV CTX-M. Results Eight bacterial species were identified, 75% (6/8) Gram Negative, 25% (2/8) Gram Positive). Escherichia coli was the most frequently isolated species 71.4% (50/70) followed by Klebsiella pneumoniae 10% (7/70), Enterobacter cloacae 5.7% (4/70, Proteus mirabilis 4.3% (3/70), Enterococcus faecalis 2.9% (3/70), Acinetobacter baumannii 2.9% (3/70), Lelliottia amnigena 1.4% (1/70) and Streptococcus agalactiae 1.4% (1/70). All 50 biochemically confirmed E. coli isolates were also confirmed using uspA gene. Three resistance genes TEM, SHV and CTX-M were detected using polymerase chain reaction. Conclusion E. coli was the most frequently isolated species followed by K. pneumoniae, this result may indicate that K. pneumoniae is becoming increasingly common as an etiological agent of UTI. A high resistance toward Amoxicillin- Clavulanic Acid was found among E. coli isolates, while multiple antibiotic/drug resistance was 62%. These results highlight the need to adhere to the therapeutic guidelines in treating UTI’s and other infections and not overuse antibiotics to prevent the emergence of multidrug-resistant bacteria.